2001
DOI: 10.1021/op010224h
|View full text |Cite
|
Sign up to set email alerts
|

Case Study of a γ-Butyrolactone Alkylation with 1,3-Dimethyl-2-imidazolidinone as a Promoter

Abstract: 1,3-Dimethyl 2-imidazolidinone (DMI) is of lower toxicological risk than 1,3-dimethyl-3,4,5,6-tetrahydro-2(1H)-pyrimidinone (DMPU), hexamethyl-phosphorus triamide (HMPT), and hexamethylphosphoramide (HMPA). Formation of dialkylation byproducts is a common problem in lactone alkylation. DMI, used in stoichiometric amount, increases the rate of alkylation of γ-butyrolactone 1 by >30-fold, therefore minimizing the dialkylation in multi-kilogram preparations. The isolated yield of the monoalkylated product 2 is >9… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
12
0

Year Published

2002
2002
2019
2019

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(13 citation statements)
references
References 18 publications
1
12
0
Order By: Relevance
“…Methylation of 11 in α-position to the C=O group by deprotonation with lithium diisopropylamide (LDA), followed by treatment with MeI, yielded 12. Instead of HMPA, 1,3-dimethylimidazolidin-2-one (DMI), which is of lower toxicological risk, was used as an additive [30]. Although Li et al used lithiumhexamethyldisilazanide as a base for similar reactions [30], we preferred LDA in the combination with DMI.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Methylation of 11 in α-position to the C=O group by deprotonation with lithium diisopropylamide (LDA), followed by treatment with MeI, yielded 12. Instead of HMPA, 1,3-dimethylimidazolidin-2-one (DMI), which is of lower toxicological risk, was used as an additive [30]. Although Li et al used lithiumhexamethyldisilazanide as a base for similar reactions [30], we preferred LDA in the combination with DMI.…”
Section: Methodsmentioning
confidence: 99%
“…Instead of HMPA, 1,3-dimethylimidazolidin-2-one (DMI), which is of lower toxicological risk, was used as an additive [30]. Although Li et al used lithiumhexamethyldisilazanide as a base for similar reactions [30], we preferred LDA in the combination with DMI. Therefore, the yield (44%) was lower than reported (70%) [31].…”
Section: Methodsmentioning
confidence: 99%
“…1 132.2,131.3*,119.0,118.6*,116.5 (q,J = 287.9 Hz),86.5,85.7*,67.4*,67.2,51.4 (q,J = 3.3 Hz),51.3,50.3* (q, J = 2.9 Hz), 50.0*,41.0*,38.3,16.4,15.74*,15.71*,15.41,15.38*,15.26,14.3*,13.4. 19 F NMR (376 MHz,CDCl3) Synthesis of (S)-2-(1-(3-Oxo-3-((R)-2,6,7,7a-tetrahydro-1Hinden-5-yl)prop-1-yn-1-yl)cyclopropyl)propyl Methanesulfonate (54). A mixture of carboxylic acid 33 (53% ee, mg, 2.44 mmol, 1.2 equiv) in dichloromethane (20 mL) and N,N-dimethylformamide (4 drops) was treated dropwise with oxalyl chloride (243 μL, 2.84 mmol, 1.4 equiv) at 0°C.…”
Section: ■ Experimental Sectionmentioning
confidence: 99%
“…While Ellman's pioneering studies have revealed that adding ester enolates to N-tert-butanesulfinyl imines result in good diastereoselectivities at the β-amino stereocenter, 19 the selectivity outcome at the α-center remains difficult to predict when fully substituted, unsymmetrical enolates are employed. Following an initial survey of imines and enolates, 20 allylated valerolactone 8 21 and sulfinyl imine 9 22 were identified as suitable precursors (Scheme 1). Thus, reaction of 9 with the lithium enolate derived from 8 led to an intriguing Mannich− retro-Mannich equilibration of the β-amino lactones (SS-10 and SR-10), and optimization studies eventually yielded an ∼1:1 mixture of C8 epimers in 82% combined yield on multigram scale.…”
mentioning
confidence: 99%